Empowerment of Indigenous Peoples Through Empowerment of Indigenous Institutions in Natural Resource Governance - JACOB, Ananias Riyoan Philip; TIRAN, Rex; MUSKANAN, Frans Wilmat (PT Keberlanjutan Strategis Indonesia, 2025)
Indigenous peoples play a vital role in the sustainable management of natural resources, drawing upon local wisdom that has been passed down through generations. Customary institutions are essential for upholding cultural values, customary law, and the management of customary forest areas that are integral to their way of life. However, forest governance policies over recent decades have frequently overlooked their contributions, restricting access to and control over indigenous territories. A notable example is the alteration of the status of customary forest areas in Mutis-Timau National Park in East Nusa Tenggara, which were historically managed by the Dawan tribe through a customary prohibition system. While the designation as a national park offers conservation advantages, it has social implications for the indigenous peoples reliant on these forests. To tackle this issue, this initiative proposes a strategy aimed at reinforcing customary institutions as the primary actors in natural resource governance, utilizing a participatory approach rooted in local wisdom. The proposed solutions include: (1) enhancing the capacity of indigenous institutions, (2) fostering collaboration between indigenous peoples and governmental bodies, (3) promoting sustainable economic development based on natural resources, and (4) providing environmental education for the younger generation within indigenous communities.